1995
DOI: 10.1136/gut.37.5.623
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal absorptive capacity, intestinal permeability and jejunal histology in HIV and their relation to diarrhoea.

Abstract: Intestinal function is poorly defined in patients with HIV infection. Absorptive capacity and intestinal permeability were assessed using 3-O-methyl-D-glucose, D-xylose, L-rhamnose, and lactulose in 88 HIV infected patients and the findings were correlated with the degree of immunosuppression (CD4 counts), diarrhoea, wasting, intestinal pathogen status, and histomorphometric analysis ofjejunal biopsy samples. Malabsorption of 3-0-methyl-D-glucose and D-xylose was prevalent in all groups of patients with AIDS b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
95
0
2

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(106 citation statements)
references
References 37 publications
9
95
0
2
Order By: Relevance
“…Keating et al observed that malabsorption and increased intestinal permeability are common in AIDS patients and that malabsorption correlated significantly with the degree of immune suppression and BMI. 8 The study findings demonstrate that adequate nevirapine levels are maintained in blood irrespective of the stage of immune suppression and BMI.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Keating et al observed that malabsorption and increased intestinal permeability are common in AIDS patients and that malabsorption correlated significantly with the degree of immune suppression and BMI. 8 The study findings demonstrate that adequate nevirapine levels are maintained in blood irrespective of the stage of immune suppression and BMI.…”
Section: Discussionmentioning
confidence: 74%
“…7 Keating et al reported that malabsorption correlates significantly with the degree of immunosuppression. 8 We undertook a study to obtain information on the pharmacokinetics of nevirapine in HIV-infected patients on treatment with FDCs in India, as well as the influence of immunological status, sex, and body mass index (BMI) on the pharmacokinetics of these drugs, as very limited information is available on this aspect. up at regular intervals.…”
mentioning
confidence: 99%
“…Serum carotene concentrations are affected by severity of HIV immune disease, gender mix of the population, recent intake and laboratory testing conditions. Besides low dietary intake, low serum carotene concentrations in HIV-infected persons may be because of malabsorption, diarrhea, altered gut barrier function, altered metabolism (Keating et al, 1995) and oxidative stress (Sappey et al, 1994;Allard et al, 1998). The extent of reduction of serum carotene is secondary to its oxidation and consequent depletion by singlet oxygen (Bendich, 1993).…”
Section: Mixed Carotenoids In Hiv Infectionmentioning
confidence: 99%
“…Uma relação entre o grau de imunodeficiência e má absorção foi relatada em adultos com AIDS (42) . Entretanto, em um grupo de crianças infectadas pelo HIV não foi encontrada associação entre baixos níveis de LTCD4+ e má absorção (40) .…”
Section: Padrão De Comportamento Da D-xilose Em Relação àS Variáveisunclassified
“…MILLER et al (52) demonstraram que a má absorção de carboidrato foi relativamente freqüente em crianças HIV positivas assintomáticas, ocorrendo em 40% dos casos. Por outro lado, KEATING et al (42) não evidenciaram má absorção intestinal em pacientes HIV positivos assintomáticos.…”
Section: Introductionunclassified